ANALISIS DAN PERANCANGAN APLIKASI CHATTING DENGAN METODE ADDIE UNTUK KOMUNIKASI DAN MONITORING WORK FROM HOME (WFH) BERBASIS WEB (STUDI KASUS PT.RJGF INTERNATIONAL) - Teguh Ari Wibowo; Alvino Octaviano (CV. Multi Kreasi Media, 2022)
In general, communication is connecting humans with one another, nowadays the way of communication between humans is very easy and advanced. The increase in this way of communication is marked by a wide variety of tools and software that are very numerous and easy to obtain so that everyone around the world can communicate well, communication through a social networking platform is also very popular with the community. To interact with each other, the Chat Application is one of the most important things in the current era considering that currently the world is facing the Covid-19 virus, the case that started in Wuhan China has now spread to all corners of the world, various efforts have been made to combat the Covid-19 virus. 19 and stop the chain of spreading the Covid-19 virus quickly, one of these efforts is to work from home (WFH). . The method used in making this chat application is the ADDIE method (Analyze, Design, Development, Implementation, Evaluation) which is used to analyze the design of the system to be made. The result of this research is that it can make it easier for employees to work from home (WFH) and communicate.